Vehicle detection and tracking for traffic management - Mallikarjun Anandhalli; Vishwanth P. Baligar; Pavana Baligar; Pooja Deepsir; Mithali Iti (IAES International Journal of Artificial Intelligence (IJ-AI), 2021)
The detection of object with respect to Vehicle and tracking is the most needed step in computer research area as there is wide investment being made form Intelligent Traffic Management. Due to changes in vision or scenes, detection and tracking of vehicle under different drastic conditions has become most challenging process because of the illumination, shadows etc. To overcome this, we propose a method which uses TensorFlow fused with corner points of the vehicles for detection of vehicle and tracking of an vehicle is formulated again, the location of the object which is detected is passed to track the detected object, using the tracking algorithm based on CNN. The proposed algorithm gives result of 90.88% accuracy of detection in video sequences under different conditions of climate.